FINANCIAL-STATISTICAL ASSESSMENT OF AGRICULTURAL PRODUCTS PRODUCTION IN THE REGION - Yusupov Faizulla Yakubovich; Mukhitdinov Khudayar Suyunovich (Scholar Express Journals, 2023)
In this article, proposals and conclusions have been developed for the analysis of financial-statistical evaluation of agricultural production in the region based on empirical modeling.
Keywords: Financial-statistical evaluation; Econometric model; Empirical modeling; Digital economy